Conversion of Oil Palm Empty Fruit Bunch (OPEFB) and Mesocarp (OPM) Fibers into Liquid Natural Coagulants and Performance Evaluation for Palm Oil Mill Secondary Effluent (POMSE) - NURLISA BINTI MOHAMAD RUZLI; NOR MAIZZATY ABDULLAH; ELIZAH MOHAMED (Progress in Engineering Application and Technology, 2026)
The palm oil industry is one of the major agricultural sectors in Malaysia and Southeast Asia, contributing significantly to economic growth while generating large volumes of liquid and solid waste during the milling process. Among these wastes, palm oil mill effluent (POME) represents the largest fractions with approximately 0.5 – 2.5 tonnes generated for every tonne of crude palm oil produced. Palm oil mill secondary effluent (POMSE) may still contain residual organic matter and suspended particles even after biological treatment, which can affect the quality of wastewater discharged into the environment. Therefore, additional treatment is required to further improve effluent quality before discharge. This study aimed to evaluate the effectiveness of liquid oil palm empty fruit bunch (OPEFB) and oil palm mesocarp (OPM) fibers as natural bio-coagulants for POMSE treatment. Liquid bio-coagulants were prepared using an alkaline extraction method with sodium hydroxide (NaOH). Fourier Transform Infrared Spectroscopy (FTIR) was used to identify the functional groups present in the liquid extracts. Jar test experiments were conducted  using 200 mL of POMSE per beaker, with bio-coagulant dosages varied from 0 to 600 mL. Water quality parameters including pH, turbidity, dissolved oxygen (DO), biochemical oxygen demand (BOD5)  and total suspended solids (TSS) were analysed. FTIR analysis confirmed the presence of dominant hydroxyl (-OH) functional groups in both liquid extracts indicating their lignocellulosic nature. At the optimum bio-coagulant dosage of 300 mL added to 200 mL of POMSE, liquid OPEFB achieved a noticeable reduction in BOD5 with removal efficiencies ranging from approximately 49% to 56% whereas liquid OPM showed limited improvement with BOD5 removal below 10%. Turbidity reduction was modest, with removals of 11.9% for OPEFB and 4.8% for OPM, while changes in TSS were minimal (